2018
DOI: 10.1161/circep.117.006019
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Multicenter Study of the Common Isthmus in Post–Atrial Fibrillation Ablation Multiple-Loop Atrial Tachycardia

Abstract: Multiple-loop ATs are complex, frequently including anatomic circuits. They have specific characteristics determined by the combination of AMAT and non-AMAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 12 publications
6
30
0
3
Order By: Relevance
“…However, the complexity of the AT mechanism and circuits can still cause a change in the propagation and transfer to another existing circuit after the ablation of the first circuit. The identification of all the loops is critical to the ablation strategy which targets the common isthmus when at least one nonanatomic loop is involved and is reported by Takigawa et al 27 to achieve acute success in terminating the tachycardia in 80%. It is therefore essential to determine whether one loop is a “functional” circuit that will keep rotating once the first loop is abolished by radiofrequency ablation of the other loop, or whether it is an “innocent” bystander that will not require additional treatment 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the complexity of the AT mechanism and circuits can still cause a change in the propagation and transfer to another existing circuit after the ablation of the first circuit. The identification of all the loops is critical to the ablation strategy which targets the common isthmus when at least one nonanatomic loop is involved and is reported by Takigawa et al 27 to achieve acute success in terminating the tachycardia in 80%. It is therefore essential to determine whether one loop is a “functional” circuit that will keep rotating once the first loop is abolished by radiofrequency ablation of the other loop, or whether it is an “innocent” bystander that will not require additional treatment 26 .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to determine whether one loop is a “functional” circuit that will keep rotating once the first loop is abolished by radiofrequency ablation of the other loop, or whether it is an “innocent” bystander that will not require additional treatment 26 . Recently, Takigawa et al 27 reported that when dual‐loop ATs included a nonanatomic loop, the common isthmus was generally short, and the ablation was successful. When the arrhythmia combined two nonanatomic loops, a complete anatomic linear ablation was usually not needed and accounted for the better outcome observed in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although reentrant tachycardia usually exhibited stable CL, its variability also could be seen sometimes, especially in complicated tachycardia. Recently Takigawa et al found 16.7% cases had CL variability in their multiple‐loop AT group, and this CL variability was more frequently observed in nonanatomic macroreentrant ATs . As for stable beat‐to‐beat CL alternation, three cases were observed by Anter et al in their 24 recurrent scar‐related ATs, and all of them showed dual‐loop reentries with figure‐of‐eight configuration .…”
Section: Discussionmentioning
confidence: 95%
“…We report a complex organized atrial arrhythmia with alternation of 2 circuits. Although dual-loop and triple-loop tachycardias have been described in post-AF ablation atria, 6 these loops coexist and share a common isthmus. To our knowledge, a tachycardia with 2 different, successive circuits has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%